Potential role of B7-1 and CD28 molecules in immunosuppression in leprosy - Agrewala, J N (Blackwell Science Inc, 1998)
In order to understand the mechanism of unresponsiveness towards Mycobacterium leprae antigens in leprosy, we evaluated the role of M. leprae sonicate antigens in regulating the expression of the costimulatory molecules B7-1, CD28, intercellular adhesion molecule-1 (ICAM-1), LFA-1α, LFA-1β and Mac-1 on the lymphocytes of both leprosy patients and healthy subjects. It was observed that the expression of B7-1 and CD28 was significantly decreased but the levels of ICAM-1 and LFA-1α were increased in patients with untreated borderline leprosy (BL)/lepromatous leprosy (LL) disease. No remarkable change was noticed in the case of borderline tuberculoid (BT) leprosy or treated BL/LL patients. Further, a striking finding was that lymphocytes from healthy subjects cultured with a particularly high dose of M. leprae sonicate antigens down-regulated the expression of B7-1 and CD28 molecules, but up-regulated the display of ICAM-1 and LFA-1α. Furthermore, proliferation induced by M. leprae sonicate was inhibited only by anti-B7-1 antibody. Mycobacterium leprae antigen-induced suppression of the proliferation of lymphocytes of healthy volunteers and LL patients was reversed by culturing the lymphocytes with purified protein derivative (PPD). It may be concluded from the findings in this study that down regulation of B7-1 and CD28 in BL/LL leprosy patients may be responsible for a defective T cell signalling by the B7-1/CD28 pathway caused by M. leprae antigens. This may lead to clonal inactivation of M. leprae-reactive T cells, consequently the bacilli grow without restriction in macrophages.